Can water float on oil? - Phan, Chi; Allen, Benjamin; Peters, Luke; Thu, Le; Tade, Moses (American Chemical Society, 2012)
The floatability of water on oil surface was studied. A numerical model was developed from the Young-Laplace equation on three interfaces (water/oil, water/air, and oil/air) to predict the theoretical equilibration conditions. The model was verified successfully with an oil/water system. The stability of the floating droplet depends on the combination of three interface tensions, oil density, and water droplet volume. For practical purposes, however, the equilibrium contact angle has to be greater than 5° so the water droplet can effectively float. This result has significant applications for biodegrading oil wastes.